Trying Again, Failing Again: Samuel Beckett and the Sequel Play. (August 2021) - Simpson, Hannah
Abstract : Samuel Beckett's Waiting for Godot has spawned several unauthorized sequel plays, which see Godot arrive on stage in 1960s Yugoslavia, 1980s Ireland, 1990s North America, and early 2000s Japan. The sequel play is a largely ignored phenomenon in literary scholarship, with the sequel form itself routinely dismissed as a derivative and inevitably disappointing text. Yet the sequel also re-situates and re-evaluates the original text, and its reiterative nature aptly parallels the paradox of non-ending in Beckett's original Waiting for Godot. Focusing on four unauthorized stage sequels to Beckett's play – Miodrag Bulatović's Godo je došao ( Godot Has Arrived, 1966), Alan Titley's Tagann Godot ( Godot Arrives, 1987), Daniel Curzon's Godot Arrives (1999), and Minoru Betsuyaku's Yattekita Godot ( Godot Has Come, 2007) – this article examines how these sequels rework the cultural logic of Godot's arrival to their own critical and political ends. These playwrights draw on the very recursive, even frustrating, nature of the sequel form itself as an exegetic framework, reproducing the trope of non-ending that characterizes Beckett's own work. Hannah Simpson is the Rosemary Pountney Junior Research Fellow in British and European Drama at St Anne's College, University of Oxford. She is currently working on two forthcoming Beckett-related monographs: Witnessing Pain: Samuel Beckett and Post-War Francophone Theatre and Samuel Beckett and Disability Performance.